Sharing Knowledge Online Lintas Fungsi sebagai Strategi Komunikasi Organisasi saat Pandemi - Husni, Mochamad (Magister of Communication Science, Sahid University Jakarta., 2022)
This research is based on the phenomenon that the management of PT Astra Agro Lestari Tbk applies the concept of a matrix organization in terms of the roles and responsibilities of public relations. The matrix pattern makes coordination happen across functions. The implementation of communication programs in the form of media relations in all subsidiaries spread across nine provinces becomes increasingly difficult when the work from home work pattern is implemented. This study wants to find out how the online sharing session strategy is carried out by the Communications and Public Affairs Division in overcoming the lack of knowledge of the Community Development Division as the field implementer of the communication program. The research method used is descriptive qualitative. Collecting data in this study using observation and interview techniques. Research concludes that online coordination can be a solution, but its effectiveness needs to be combined with cultural elements and formal strengths.